2019
DOI: 10.1073/pnas.1903315116
|View full text |Cite
|
Sign up to set email alerts
|

Extended high-frequency hearing enhances speech perception in noise

Abstract: Young healthy adults can hear tones up to at least 20 kHz. However, clinical audiometry, by which hearing loss is diagnosed, is limited at high frequencies to 8 kHz. Evidence suggests there is salient information at extended high frequencies (EHFs; 8 to 20 kHz) that may influence speech intelligibility, but whether that information is used in challenging listening conditions remains unknown. Difficulty understanding speech in noisy environments is the most common concern people have about their hearing and usu… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

13
92
3

Year Published

2020
2020
2024
2024

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 142 publications
(121 citation statements)
references
References 61 publications
13
92
3
Order By: Relevance
“…Previous studies 4 have identified that hearing loss, as measured by the pure-tone audiogram, is a strong correlate of SiN ability among people with hearing loss, and may also explain some of the variability in SiN performance among people who have audiometric thresholds at clinically measured frequencies (0.25–8 kHz) in the normal hearing range. There is also evidence that extended high-frequency hearing (8–20 kHz) can enhance SiN perception 19 . Although pure-tone audiometric thresholds may be used synonymously with ‘hearing loss’, this test measures tone-sensitivity in quiet, which is different from SiN.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Previous studies 4 have identified that hearing loss, as measured by the pure-tone audiogram, is a strong correlate of SiN ability among people with hearing loss, and may also explain some of the variability in SiN performance among people who have audiometric thresholds at clinically measured frequencies (0.25–8 kHz) in the normal hearing range. There is also evidence that extended high-frequency hearing (8–20 kHz) can enhance SiN perception 19 . Although pure-tone audiometric thresholds may be used synonymously with ‘hearing loss’, this test measures tone-sensitivity in quiet, which is different from SiN.…”
Section: Discussionmentioning
confidence: 99%
“…Here, we were interested in SiN in people with normal hearing and we utilised a stringent criterion to exclude participants with mild tone sensitivity impairment in the high-frequency range. We did not measure audiometric thresholds above 8 kHz, which may have some effect on SiN 19 because these thresholds are not measured routinely in clinical practice. Although, there was a relationship between high-frequency (4–8 kHz) audiometric thresholds and SiN in the full sample, consistent with the results of Holmes and Griffiths 4 , we did not find a significant correlation between audiometric hearing thresholds and SiN performance after excluding participants with audiometric thresholds > 15 dB HL.…”
Section: Discussionmentioning
confidence: 99%
“…Badri et al (2011) showed that listeners who self-reported and exhibited speech-in-noise difficulties had elevated EHF thresholds at 12.5 and 14 kHz compared with a control group. Motlagh Zadeh et al (2019) also found grouplevel differences in self-reported speech-in-noise difficulty, with greater likelihood of reporting difficulty for groups with more severe EHF hearing loss (measured at 10, 12.5, 14, and 16 kHz). They also reported a correlation between EHF pure-tone averages (PTAs) and speech-in-noise scores when the noise masker was a broadband speech-shaped noise, although, surprisingly, no such relationship was observed when the noise masker was bandlimited to 8 kHz.…”
mentioning
confidence: 82%
“…For example, the average young, normal-hearing listener can detect the absence of speech energy beyond approximately 13 kHz, although listeners with better 16-kHz pure-tone thresholds can detect losses at even higher frequencies ( Monson & Caravello, 2019 ). It has also been demonstrated that EHF audibility contributes to speech localization ( Best et al., 2005 ), speech quality ( Monson et al., 2014b ; Moore & Tan, 2003 ), talker head orientation discrimination ( Monson et al., 2019 ), and speech recognition in the presence of background speech ( Monson et al., 2019 ) and noise ( Motlagh Zadeh et al., 2019 ).…”
mentioning
confidence: 99%
“…Computer-based sensory and cognitive training has long held the promise of dramatic improvements on real world abilities. However, finding an auditory training task that successfully leads to improved speech perception in noise, a frequently reported auditory disability 1 , 2 , remains elusive. Two problems have frequently occurred when training paradigms meant to improve such skills have been examined via carefully controlled experiments.…”
Section: Introductionmentioning
confidence: 99%